Respuesta :
Answer:
(m-16)(m+4)
Step-by-step explanation:
To factor a quadratic expression
First write the variable in each parentheses, then put negative/ positive, after that ask yourself what numbers have the product of the coefficient of x^0 and the sum of x^1.
David correctly factored the expression m^2 - 12m - 64 and got (m - 16)(m + 4).
How to factor an equation?
An equation can be factored into its factors by splitting the middle term of the equation.
The given expression can be factored as shown below:
m^2 - 12m - 64 = 0
⇒ m^2 - 16m +4m - 64 = 0
⇒ m(m - 16) + 4(m - 16) = 0
⇒ (m + 4)(m - 16) = 0
The factors of the equation m^2 - 12m - 64 = 0 are (m - 16)(m + 4).
Therefore, we have found that David correctly factored the expression m^2 - 12m - 64 and got (m - 16)(m + 4). The correct answer is option C or (3).
Learn more about factorization here: https://brainly.com/question/25829061
#SPJ2